Ixeris dentata extract regulates salivary secretion through the activation of aquaporin-5 and prevents diabetes-induced xerostomia - Bhattarai KR; Lee SW; Kim SH; Kim HR; Chae HJ (Dove Medical Press, 2017)
Kashi Raj Bhattarai,1 Sang-Won Lee,2 Seung Hyun Kim,3 Hyung-Ryong Kim,4 Han-Jung Chae1 1Department of Pharmacology and Institute of New Drug Development, School of Medicine, Chonbuk National University, Jeonju, 2Department of Herb Crop Resources, National Institute of Horticultural and Herbal Science, Rural Development Administration, Eumseong-gun, 3College of Pharmacy, Yonsei Institute of Pharmaceutical Science, Yonsei University, Incheon, 4Graduate School, Daegu Gyeongbuk Institute of Science and Technology, Daegu, Republic of Korea Abstract: The aim of this study was to investigate the effects of Ixeris dentata (IXD) extract to improve the salivation rate in dry mouth induced by diabetes. Both control and diabetic rats were treated with a sublingual spray of either water or IXD extract to determine the effects of IXD on salivation. During the study, we observed that IXD extract treatment increased the salivary flow rate in diabetic rats. The expression of α-amylase was increased significantly in both saliva and glandular tissue lysates of IXD-treated diabetic rats. Aquaporin-5 protein expression was abnormally low in the salivary glands of diabetic rats, which increased hyposalivation and led to salivary dysfunction. However, a single oral spray of IXD extract drastically increased the expression of aquaporin-5 in salivary gland acinar and ductal cells in diabetic rats. Moreover, IXD extract induced expression of Na+/H+ exchangers in the salivary gland, which suggests that Na+/H+ exchangers modulate salivary secretions and aid in the fluid-secretion mechanism. Furthermore, transient treatment with IXD extract increased the intracellular calcium in human salivary gland cells. Taken together, these results suggest the potential value of an IXD extract for the treatment of diabetes-induced hyposalivation and xerostomia. Keywords: Ixeris dentata, hyposalivation, amylase, aquaporin-5, xerostomia, diabetes